2020
DOI: 10.3389/fpsyt.2020.00614
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Default Mode Network Connectivity and Its Association With Social Cognition in Adolescents With Autism Spectrum Disorder and Early-Onset Psychosis

Abstract: Recent studies have demonstrated substantial phenotypic overlap, notably social impairment, between autism spectrum disorder (ASD) and schizophrenia. However, the neural mechanisms underlying the pathogenesis of social impairments across these distinct neuropsychiatric disorders has not yet been fully examined. Most neuroimaging studies to date have focused on adults with these disorders, with little known about the neural underpinnings of social impairments in younger populations. Here, we present a narrative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 133 publications
6
55
0
Order By: Relevance
“…Abnormal functional connectivity in the DMN have been reported in autism-related studies [34,45], and weaker intrinsic connectivity in the DMN is associated with poorer social skills of ASD [14,23].The present study also observed weakened entropy connectivity between VPCC (BA 23) and VACC (BA 24) in the DMN of ASD. This under-connectivity might induce abnormal emotional processing and self-awareness disorders of patients with ASD.…”
Section: Abnormal Entropy Connectivity In the Dmnsupporting
confidence: 75%
See 1 more Smart Citation
“…Abnormal functional connectivity in the DMN have been reported in autism-related studies [34,45], and weaker intrinsic connectivity in the DMN is associated with poorer social skills of ASD [14,23].The present study also observed weakened entropy connectivity between VPCC (BA 23) and VACC (BA 24) in the DMN of ASD. This under-connectivity might induce abnormal emotional processing and self-awareness disorders of patients with ASD.…”
Section: Abnormal Entropy Connectivity In the Dmnsupporting
confidence: 75%
“…It's similar to the theory of weak central coherence [33] The under-connectivity theory has been supported by subsequent studies. These investigations nd that the weakened functional connection between the medial prefrontal cortex (mPFC) and posterior cingulate cortex (PCC) results in a decrease in the level of social cognition [22,34] and the lack of functional connections between the frontal and posterior cortex (i.e., the parietal, occipital, and temporal lobes) in individuals with ASD contributes to poor performance for complex cognitive tasks such as language comprehension, social interaction, and working memory [35][36][37]. In addition, under-connectivity of the brain structural network such as abnormalities of white matter tracts (corpus callosum, arcuate fasciculus, inferior frontal-occipital fasciculus, etc.)…”
Section: Weakened Entropy Connectivity In the Cenmentioning
confidence: 99%
“…The lack of group differences for seeded regions in the DMN and CEN is surprising given the widespread evidence for altered connectivity in these networks across age groups 31,33,35,37,57 . One study of male highfunctioning ASD adults found hypoconnectivity between core DMN regions that negatively correlated with AQ 36 .…”
Section: Discussionmentioning
confidence: 97%
“…We additionally used a cortical seed-based approach for analyzing thalamocortical FC 18 and included seeds from the medial prefrontal cortex (mPFC), posterior cingulate cortex (PCC), and left dorsolateral prefrontal cortex (dlPFC). These seeds allowed us to examine FC in the two most commonly studied resting state networks in ASD, default mode (DMN) [35][36][37] and central executive (CEN) [38][39][40][41][42] . These networks have shown altered connectivity with sensorimotor regions in previous studies of adolescents with ASD 37 and are known to engage the thalamus as a key functional region 27,43 .…”
Section: Introductionmentioning
confidence: 99%
“…Other neural networks described as possible protagonists in the SC process in ASD and SSD are the Default Mode Network (DMN) and the Salience Network (SN). The DMN is a major network encompassing the medial PFC, PCC, precuneus and bilateral inferior parietal lobules, which is activated when there is no engagement in any specific task and deactivated in the context of effortful cognitive tasks and SC tasks ( 115 – 118 ). The SN is a task activated brain network and comprises the anterior insula, dorsal ACC, the anterior PFC and the thalamus ( 119 ).…”
Section: Introductionmentioning
confidence: 99%